¿Qué tan importante es la estética en la salud? Análisis del tratamiento con láser en los cuidados de la piel - Amán, Marisol (2017)
Context: importance of aesthetic medicine in health and options most requested by patients.Objective: to determine the types of laser treatments used most frequently in the Redux Aesthetic Clinic, patient characteristics and parameters used with the Synus Novadiode 810T laser equipment, from August 2010 to July 2011.Subjects and methods: 238 patients were attended, in which 432 operations were performed with a range of 2 to 7 attentions per patient. Because skin phototype IV was predominant (96% of cases), the minimum parameters recommended by the equipment manufacturer were used, increasing to a maximum of fluences according to the type and skin tone and the individual sensitivity of each patient.Results: attention in women prevailed (range of 3: 1), noting the growing concern of the male sex regarding the care of their skin. Regarding age, the average was 37 years with a range of 25 years to 50 years, which indicates that interest in skin care, especially facial when the third decade of life elapses. They emphasize the combined treatments (18.9%), dyschromias (18%), elimination of moles (14.3%) and rejuvenation (13%).Conclusion: there is a growing concern in women, regarding the care of their skin, especially facial when the third decade of life, where the combined treatment of dyschromias with scarring, telangiectasia or expression lines is more frequent. In addition, the important demand for laser treatments must be considered, with the month of August receiving the most attention being attributed to the holiday period in the sierra region.